The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.2337/diabetes.52.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Purified Allogeneic Hematopoietic Stem Cell Transplantation Blocks Diabetes Pathogenesis in NOD Mice

Abstract: Purified hematopoietic stem cells (HSCs) were transplanted into NOD mice to test whether development of hyperglycemia could be prevented. Engraftment of major histocompatibility complex-mismatched HSCs was compared with bone marrow (BM) grafts. HSCs differed from BM because HSCs were more strongly resisted and HSC recipients retained significant levels of NOD Tcells, whereas BM recipients were full donor chimeras. Despite persistent NOD T-cells, all HSC chimeras were protected from hyperglycemia, and attenuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
148
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(155 citation statements)
references
References 36 publications
7
148
0
Order By: Relevance
“…Interestingly, however, pancreatic isoantigens were previously detected in rabbits [54]. Hence, split tolerance is potentially relevant to chimerism strategies in islet [55] or pancreas transplantation that is currently used to treat type-1 diabetes. Supporting this possibility, we recently found that mixed chimerism generated in pre-diabetic NOD mice does lead to split tolerance, with donor islets being rapidly rejected (Chan et al, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, however, pancreatic isoantigens were previously detected in rabbits [54]. Hence, split tolerance is potentially relevant to chimerism strategies in islet [55] or pancreas transplantation that is currently used to treat type-1 diabetes. Supporting this possibility, we recently found that mixed chimerism generated in pre-diabetic NOD mice does lead to split tolerance, with donor islets being rapidly rejected (Chan et al, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…And Judy Shizuru and I showed that C57BL-to-BALB/c chimeras had better minor histocompatibility T cell restriction to donor H2 b MHC than to thymic host (H2 d ) MHC, apparently contradicting the rules for MHC restriction established previously (15). Finally, we have shown that tolerance induction by HSCs from donors genetically resistant to diabetes and lupus can end the autoimmune components of these diseases in mice (18)(19)(20).…”
Section: Introductionmentioning
confidence: 97%
“…We can measure and visualize proteins in amounts that were unimaginable 10 years ago. Numerous studies utilized GFP to track cell fate following bone marrow transplantation, local injection or promoter specific expression [3][4][5][6][7][8][9][10]. While a variety of groups showed that GFP-expressing bone marrow cells are able to seed many tissues and *corresponding author ztoth@mail.nih.gov, mezeye@mail.nih.gov, NIH, NIDCR, Bldg 49, Rm 5A-76, 49 Convent Drive, Bethesda, Md 20892, T: (301) 435-5635, F: (301) 496-1339 Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication.…”
Section: Introductionmentioning
confidence: 99%